Entrepreneurship has Emerged as the Economic Engine and Social Development throughout the World - Kefela, Ghirmai T (Journal of Asian Business Strategy, 2011)
This paper consists of an introductory survey of two fundamental questions regarding the link between international entrepreneurship and economic growth. The first step in establishing the linkages requires the formulation of knowledge about the psychological make-up of entrepreneurs. The paper explains that Entrepreneurial activity breeds innovation, injects competitive pressures and develops opportunities in economies. It is the foundation in many respects for broader economic development. Entrepreneurship polices are equally important, as an engine of innovation, in developed countries as they are in developing or transition economies. The purpose of this paper is to explain why the model of the entrepreneurial economy maybe a better frame of reference than the model of the managed economy when explaining the role of entrepreneurship in the contemporary, developed economies. While borrowing constraints or other financial frictions affect entrepreneurship productivity and the distribution of income by restricting agents from profitable occupations that require capital, such as entrepreneurship, this paper is devoted to exploring issues aiming to increase national wealth and to improve international competitiveness of the national economy.